Advanced Drug Delivery Systems - Prajapati, Bhupendra (IntechOpen, 2023)
The physicochemical properties of drugs limit their delivery in terms of absorption, circulation, residence time, and so on, which in turn impacts the pharmacokinetics, pharmacodynamics, toxicity, immunogenicity, and efficacy of these drugs. Various advanced drug delivery systems can overcome such issues and improve therapeutic efficacy. Recent developments in novel drug delivery systems have opened new avenues to providing the safest, most effective, and most stable dosage forms. This book discusses advanced drug delivery systems, including oraganogels, transdermal delivery systems for chronic and acute pain, ocular systems, nanosponges for cancer targeting, and much more.